(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Masyudi, Hanafiah M, Rinidar, Usman S, Marlina. 2022. Phytochemical screening and GC-MS analysis of bioactive compounds of Blumea balsamifera leaf extracts from South Aceh, Indonesia. Biodiversitas 23: 1344-1352. Blumea balsamifera is a traditional herbal medicine that has been used worldwide. It is also known as Capa leaf in Aceh, Indonesia. B. balsamifera has been used by the local community for wound healing, anti-bacterial, and anti-inflammation. However, there is no study so far attempting to identify the chemical compounds of B. balsamifera leaves from Aceh. The present study thus aimed to analyze the chemical compounds of B. balsamifera leaves from Aceh. In this study, the B. balsamifera leaves were collected from Gunongpulo village, South Aceh, Indonesia. The extraction process was performed using the maceration method. The active chemical compounds in the B. balsamifera leaf extracts with n-hexane, ethyl acetate, and ethanol solvents were analyzed through phytochemical screening, Fourier Transform Infrared (FTIR) Spectroscopy Analysis and GC-MS. The results showed that B. balsamifera leaf extracts with ethanol and ethyl acetate solvents contain saponins, flavonoids, phenolics, tannins, and steroids, identified through the phytochemical screening. Meanwhile, the extract of B. balsamifera leaves with n-hexane solvent was found to contain steroids, phenolics, and tannins. Twenty-four chemical compounds in the B. balsamifera leaf extract with ethanol were identified using GC-MS. Twenty-eight and twenty-seven chemical compounds were also identified in the B. balsamifera leaf extracts with ethyl acetate and n-hexane solvents, respectively. The most abundant compounds found in the B. balsamifera leaf extracts with ethanol, ethyl acetate, and n-hexane solvents were 2,5-Dimethoxyacetophenone (11.61%), Borneol (14.48%), and Jasmoline (14.32%), respectively. These compounds are members of the flavonoid group which are effective for antibacterial, anti-inflammation, and wound healing applications.